(untitled) (Libellarium: journal for research in the field of information and related sciences, 2009)
The paper investigates the promotion of books through advertising in the newspapers published in Osijek in the second half of the 19th century. From late 18th century and in the course of the 19th century’s intense developments in the publishing of newspapers and journals, advertising in this medium was one of the ways to promote books. Booksellers and publishers advertised books in newspaper ads, relying on the fact that newspapers had become a common and omnipresent medium for disseminating information. Book advertisements were evidence of the position of books in relation to other aspects of culture and society, of the approach to their promotion and, finally, of the importance of book promotion. In order to investigate how and how much book ads were present, and how Croatian books were promoted and reached the readership, the paper analyses daily and monthly publications, such as Esseker allgemeine illustrierte Zeitung from 1869, Die Drau from 1968 to 1877, and Branislav from 1878. Among the eleven different papers published in the second half of the 19th century in Osijek, these were selected for their content, as they were the first illustrated newspapers (Esseker allgemeine illustrierte Zeitung). The investigation focused on the influence of the newly emerged illustrated press and on the influence of the newspapers published in Croatian language (Branislav), as a possible tool for spreading and promotion of Croatian books. Another focus was on the influence of continued publication and on the growth of a steady readership (Die Drau). The papers were analysed with the aim to locate book advertisements which were then subjected to content analysis. Also provided is a brief overview of the book production and publication in Croatia and in Osijek at the time, and an overview of the emergence of newspapers in Osijek with a brief account of the titles selected for study in order to gain an insight into the context in which book ads appeared. It was found that book advertising coincided with the emergence of newspapers, with ads at first appearing only occasionally, but later, with the development and spreading of newspapers, more frequently. Book ads were not, for the most part, included in the sections reserved for advertising but, rather, in the sections covering cultural matters, notices, daily news, etc. Visually, they were not prominent and were addressed at the existing readership, especially in the German newspapers. They may be divided into several categories: ads for books published outside Osijek and Croatia, ads for books available in Osijek’s bookshops, ads for newspapers and journals, and printers’ ads. Only a small number of book ads were printed in the ads section. Information included in the ads covered the title, author’s name, content, price, publisher and the name of the bookseller. Attached is a bibliography of advertisements in the above-listed newspapers.